The Relationship Between Public and Private Investment - Sharon J. Erenburg (Levy Economics Institute of Bard College, 1993)
The relationship between government spending and aggregates such as output, employment, and prices has been the subject of many theoretical and empirical studies. Recently, however, interest has shifted to government spending on the provision of public capital (measured as fixed, nonresidential government capital) and various indicators of economic performance. Hence, government spending is now recognized to extend beyond the traditional view of strictly purchasing goods and services: The provision of public infrastructure has become an integral component. Erenburg finds that empirical estimates from the short-run, first-difference model indicate that each additional one percentage point increase in public infrastructure and government investment spending is associated with an approximate three-fifths of a percentage point increase in private of a percentage point increase in private sector equipment were obtained by using the Stock-Watson method for testing for long-run relationships when variables are integrated of higher order, including different orders. These estimates indicate an increase of approximately two-fifths of a percentage point in private equipment investment per year. Projections reveal that if the rate of growth of public capital stock had continued from 1966 through 1987 at the 1947-1965 average annual growth rate (instead of decreasing), the growth rate of private sector equipment investment would have been between 4 to 6 percentage points above the actual rate of growth. In addition to the impact on economic growth, Aschauer (1989) and Erenburg (1993) find a positive correlation between the public provision of infrastructure and private investment. As private investment activity enhances future growth of real income, these statistical results confirm that public policy has permanent effects on real output. The empirical results confirm that public policy has permanent effects on real output. The empirical results indicate that private sector equipment investment is inversely related to government investment spending and directly related to the existing public capital stock. Also, private equipment investment is much more sensitive to public provision of capital than either structures investment. These findings suggest that public infrastructure has an overall stimulative effect on private investment activity in the United States: In essence, these results verify Aschauer's, while addressing concerns of spurious correlation.
Keywords: 330